Resistance status of Aedes mosquitoes as dengue vectors and the potential of plant larvicides from Indonesia for biological control: A narrative review - Kasman, Kasman; Ishak, Hasanuddin; Alam, Gemini; Amiruddin, Ridwan; Hastutiek, Poedji; Arsin, Andi A.; Nasir, Sudirman; Ridha, Muhammad R.; Wahid, Isra (Narra J, 2025)
Dengue fever remains a major public health threat in Indonesia, exacerbated by rising insecticide resistance in Aedes aegypti. Strategies relying on chemical insecticides, while initially effective, have led to widespread resistance in mosquito populations. This resistance is particularly pronounced in areas such as Java, where the extensive use of insecticides, including organophosphates and pyrethroids, has been documented. To address this challenge, one promising alternative is the utilization of biolarvicides derived from local Indonesian plant materials. Biolarvicides are environmentally friendly, safe, and have the potential to mitigate the adverse impacts associated with chemical insecticides. Numerous studies have explored the larvicidal properties of indigenous plants native to Indonesia, demonstrating their efficacy against A. aegypti. The aim of this study was to examine insecticide resistance in Aedes mosquitoes across Indonesia, highlighting geographical variations and underexplored regions, and exploring plant-based biolarvicides as sustainable alternatives.  Biolarvicides derived from native Indonesian plants could be eco-friendly alternative for dengue vector management. Their integration into existing control strategies could significantly enhance efforts to control dengue while reducing the environmental and health risks posed by chemical insecticides.